Strategies for development of climate resilient and high yielding hybrids and varieties in castor (Ricinus communis L.): Strategies for development of climate resilient and high yielding hybrids and varieties in castor (Ricinus communis L.) - T MANJUNATHA; C LAVANYA; S SENTHILVEL (Journal of Oilseeds Research, 2023)
Castor yields depend not only on nature of sex expression but also resistance to biotic and abiotic stress. Changing climatic conditions like temperatures and rainfall patterns are adversely affecting sex expression pattern in parents and thereby seed quality and yielding ability of castor cultivars. Mutational breeding approaches are the best for generating desirable variability in pistillate lines. S-type pistillate lines containing dominant and epistatic genes for pistillateness and temperature sensitive recessive genes for the expression of Interspersed staminate Flowers (ISFs) are the most suitable pistillate lines. Male parent with the presence of both male and female flowers in each of the basal 3-6 whorls even under cooler temperatures are feasible to ensure pollination during hybrid seed production and also optimum maleness in castor cultivars. Diverse strategies are required for the development of parents, hybrids and varieties for rainfed and irrigated conditions.